The impossibility of the triple helix. (1st September 2020) - Andersson, David Emanuel; Andersson, Åke E
Abstract : A dynamic model that distinguishes between slow and fast processes shows that a triple helix model is impossible as a tool for promoting interdependencies among science, industry and government. We present a theorem to demonstrate that a triple helix strategy is logically impossible as a means of funding scientific research in universities. In spite of this logical impossibility, national and regional triple helix strategies to improve productivity and innovative capacity have been favoured by politicians of almost every ideological stripe. Coordination of science and industry by governments is not new; it harks back to the mercantilism of seventeenth-century Britain and France. In the twentieth and twenty-first centuries, triple helix policies have led to a short-term bias in favour of applied technological research. Several examples, ranging from the military use of scientists in World War II to Chinese high technology parks show how triple helix strategies tilt playing fields, suppress academic freedom0 and expose scientists to the whims of politicians.